Coinfection of Strongyloides stercoralis and Aspergillus sp. - Marjan Motamedi; Lida Haghighi; Mostafa Omidian; Bahador Sarkari (Interdisciplinary Perspectives on Infectious Diseases)
Background. Strongyloides stercoralis has the ability to proliferate in its hosts for a long time. In most patients with a competent immune system, the infection remains asymptomatic. Objectives. Herein, we report a case of concomitant infection of Strongyloides and Aspergillus. Similar cases reported previously were reviewed in the literature and discussed in terms of diagnosis, clinical presentation, and treatment. Methods. The patient was a 55-year-old man who had a medical history of two masses in his lung and was treated with corticosteroids six months before the presentation. Results. Using the parasitological methods, massive actively motile larvae of S. stercoralis were seen in the patient’s faecal sample. Aspergillus infection was isolated from his fresh bronchoalveolar lavage (BAL) sample and confirmed by observing the septate, dichotomously branched hyphae in direct microscopic examination and also the isolation of the fungus from the culture medium. Molecular analysis revealed that the fungal species isolated from the patient are A. flavus and A. niger. Conclusion. The case highlights the features of concomitant infection of S. stercoralis and Aspergillus in immunocompromised patients and the importance of screening patients for strongyloidiasis before initiation of immunosuppressive therapy.